Impact of Community Socioeconomic Characteristics on Emergency Medical Service Delays in Responding to Fatal Vehicle Crashes - Sachi Verma, B.Tech-M.Tech, CPH, MPH; Fernando Wilson, BA, PhD; Hongmei Wang; Lynette Smith; Hyo Jung Tak (Elsevier, 2023)
Introduction: This study aimed to determine the impact of community socioeconomic status on emergency medical services' response time for fatal vehicle crashes. Methods: Authors used the 2019 National Highway Traffic Safety Administration Fatality Analysis Reporting System and 2019-2020 Area Health Resource Files to obtain emergency medical services' time intervals and county socioeconomic characteristics (e.g., median household income, availability of trauma centers, and rurality), generating a study sample of 18,540 individuals involved in fatal vehicle crashes between January and December 2019. Generalized linear models with log-link and Gamma-family were used to obtain estimates, and other variables were adjusted in the model. Results: Both the mean time of the emergency medical service arrival to the site of the crash and the mean transport time from the crash site to hospital varied by county SES. Counties with a higher mean household income had 12% shorter emergency medical services' arrival times and up to 7% shorter emergency medical services' hospital transport times than counties with lower SES. The emergency medical services' hospital transport times by emergency medical services also varied by proximity to trauma centers and were 15% shorter in counties that had ≥2 trauma centers than in counties without trauma centers. Conclusions: This study shows socioeconomic disparities in emergency medical service rescue time for fatal vehicle crashes. Community characteristics play a major role in emergency medical services' arrival time intervals. Prior research demonstrated a strong link between the timeliness of emergency medical service response and the likelihood of survival in fatal motor vehicle accidents. These findings showing that socioeconomically disadvantaged areas and those lacking trauma facilities had slower emergency medical service rescue times, suggest that socioeconomic status may be a predictor of mortality in fatal motor vehicle accidents. Effective emergency medical services are essential to reduce the morbidity and mortality among motor vehicle crash victims; however, disparities exist in the timeliness of these services by geographic and socioeconomic county characteristics. Further research is urgently needed to inform policy interventions.